Compulsive Eating - Panagiotopoulos, Nikolas; Mousama, Rania (Open Schools Journal for Open Science, 2024)
In our presentation we will talk about compulsive eating. More specifically, we will talk about the causes that could possibly start this problem, as well as the possible consequences it may have for the individual. Also, we will refer to possible solutions to deal with compulsive eating.